Diagnostic Techniques in Industrial Engineering - Ram, Mangey; Davim, J. Paulo; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book presents the most important tools, techniques, strategy and diagnostic methods used in industrial engineering. The current widely accepted methods of diagnosis and their properties are discussed. Also, the possible fruitful areas for further research in the field are identified.
Centred maintenance.- Computer interfaces.- Complex system.- Decision analysis.- Engineering economy and cost estimation.- Error tolerance.- Facility location, layout, design, and materials handling.- Fault-tree analysis, human -- Flexible manufacturing system.- Hazard and risk assessment and mitigation.- Hierarchical task analysis.- Human error assessment.- Human factors integration -- Industrial control systems.- Manufacturing, control, and automation -- Multi-view modelling.- Operations management simulation.- Process engineering.- Safety analysis.- Safety critical interactive systems.-  Sustainable engineering and development.- System evolution.- System modelling.- Systemic approach.- Systems and service modeling and simulation.
Keywords: Industrial engineering; Production engineering; Mechanical engineering; Control engineering; Industrial and Production Engineering; Mechanical Engineering; Control and Systems Theory